Definitions and Terminology: What Is Continuous Cover Forestry in Fennoscandia? - Brunner, Andreas; Valkonen, Sauli; Goude, Martin; Hanssen, Kjersti Holt; Erefur, Charlotta (Springer Nature Switzerland, 2025)
Definitions of continuous cover forestry (CCF) vary among countries, and are often a political compromise. We offer a common definition of CCF for this book, which can be found in a text box below. The three silvicultural systems included in CCF are described briefly. Conversion to CCF will be an important activity in the near future, but approaches to and experiences of conversion to CCF are largely lacking in Fennoscandia. Methods need to be developed for how to assess the suitability of forest stands for CCF or conversion to CCF. Bad practices and experiences with selective cutting in Fennoscandia before 1950 have led to a loss of experience and willingness to apply CCF. Climate adaptation will make it necessary to modify CCF approaches in the region, especially given the limited number of shade-tolerant species.
Keywords: silvicultural systems; selection system; shelterwood system; group system; conversion